Geopolitical Effect: Investor Sentiment And Stock Returns Admist Israeli-Palestinian Conflict - Muhammad Cholil; Ari Prasetyo; Mohd Syakir Bin Mohd Rosdi; Hesti Eka Setianingsih; Nurul Fauziyah; Fuad Hasyim (Faculty of Economics, Universitas Sriwijaya, 2025)
The Israeli–Palestinian conflict represents a major geopolitical event that can trigger uncertainty and volatility in global financial markets. This study investigates the impact of the conflict on investor sentiment and stock returns by comparing the stability of sharia and conventional stock markets in five Southeast Asian countries (Indonesia, Malaysia, Singapore, Thailand, and the Philippines). Using an event study approach with a 101-day event window surrounding October 7, 2023, this study examines abnormal returns before and after the conflict escalation. The findings reveal that conventional stock markets exhibit more frequent significant abnormal returns, indicating higher sensitivity to geopolitical shocks, whereas sharia stock markets demonstrate greater stability with fewer significant reactions. Furthermore, while no significant difference in abnormal returns is found in conventional markets before and after the event, sharia markets show a significant difference, suggesting a more controlled but responsive reaction to new information. These results extend the risk-as-feelings theory by showing that emotional responses to geopolitical uncertainty are more contained within sharia-compliant investment frameworks. The study contributes to the literature by providing comparative evidence from Southeast Asia and offers practical insights for investors seeking more resilient investment strategies during periods of geopolitical instability.